Regional Language Studies. Newfoundland, Number 07 (22 June 1976) - Butler Aldus, Judith; Paddock, Harold J., 1937-; Thomas, Gerald (Memorial University of Newfoundland. Folklore and Language Archive, 1976)
Linguistic research in Newfoundland / Harold Paddock -- Anglo-Irish dialects: a bibliography. Enlarged version / Judith Butler Aldus -- Some examples of blazon populaire from the French tradition of Western Newfoundland / Gerald Thomas.